School geography and the place: a knowledge’s construction in the teaching/learning geography process - Carvalho Sobrinho, Hugo de (Geosaberes; Vol 9 No 17 (2018): Jan - AprDO - 10.26895/geosaberes.v9i17.625, 2017)
This article aims to highlight the place category in the spatiality’s comprehension, to give visibility to the construction of meanings lived by a given community, in a given place, capable of understanding its own totality and, consequently, of the apprehension of the production’s process and reproduction of the space itself. Researches show that it is possible to attribute meanings to the contents of Geography by means of the identification and analysis of the phenomena experienced in the daily life lived by the students and their subsequent relation with other contexts, in other scales. The methodology used for its elaboration is based on the qualitative perspective, whose bibliographic research is based on authors who research the School Geography. In this sense, the work is divided into three interrelated moments. The preference of this theme is related to the search for possibilities and methodological propositions more consistent with the process of teaching/learning Geography.
Keywords: Categoria Lugar, Geografia Escolar, Significados.